دراسة تأثير نسبة قيمة COD إلى قيمة BOD5 لمياه الصرف على كفاءة المعالجة البيولوجية في محطة معالجة مياه مجاري مدينة حمص - رصين زكية; قمر المصطفى (Tishreen University, 2019)
Research deals with the work of Homs sewage treatment plant, which treats wastewater from civil consumption, and some other facilities located in Homs city. This plant uses biological treatment units operating by traditional activated sludge systems. COD and BOD5 are important indicators in determining the degree of sewage pollution and the development of design standards for the construction and operation of biological treatment units. Research is a statistical study that examined the effect of COD to BOD5 ratio on the efficiency of biological treatment (BOD5 removal efficiency). The daily values ​​of COD and BOD5 were recorded in the laboratory records of the plant. The relationship between efficiency values and the COD to BOD5 ratio, which gives the maximum efficiency during each of the months covered by the study from 2007 to 2011 was represented by a diagram for each year. Homs' wastewater COD / BOD5 ratio was in the range of (1.2-4.4), it is easily biodegradable wastewater. The values ​​of the BOD5 removal efficiency during these five years ranged from 70.4% to 99.5% . The statistical study by SPSS shows that the biological treatment efficiency is better within the range (1,2-3) of COD / BOD5, but also showed that the effect of this ratio on BOD5 removal efficiency was decreased during the period (2007-2011) due to the regularity of the plant operation and the stability of population status and the quality and quantity of the inflows coming to the plant. Efficiency is also related to many variables, the most important of which are the parameters of operation of the aeration tanks. يتناول البحث عمل محطة معالجة مياه مجاري مدينة حمص التي تعالج مياه الصرف الصحي الناتجة عن الصرف الصحي المعاشي وعن بعض المنشآت والورش الأخرى الموجودة في مدينة حمص، تستخدم هذه المحطة وحدات معالجة بيولوجية عاملة بالحمأة المنشطة التقليدية. يعتبر مؤشري COD وBOD5 من المؤشرات الهامة في تحديد درجة تلوث مياه المجاري ووضع المعايير التصميمية لبناء وتشغيل وحدات المعالجة البيولوجية. البحث عبارة عن دراسة إحصائية تم من خلالها دراسة تأثير النسبة COD/BOD5 على كفاءة المعالجة البيولوجية (كفاءة إزالة BOD5 )، حيث أخذت القيم اليومية لكل من مؤشري COD وBOD5 المدونة في السجلات المخبرية للمحطة، وتمت دراسة علاقة النسبة COD/BOD5 مع قيم الكفاءة  اليومية كما أخذنا بعين الاعتبار النسبة التي تعطي الكفاءة الأعظمية خلال كل شهر من أشهر السنوات ضمن الفترة التي تغطيها الدراسة من 2007 وحتى 2011، وتم تمثيل العلاقة بينهما بالشكل بياني لكل سنة. تراوحت نسبة COD/BOD5 لمياه مجاري مدينة حمص ضمن المجال (1.2-4.4) وهي بالتالي تعتبر قابلة للتحلل البيولوجي بشكل كبير حيث كانت كفاءة إزالة BOD5 خلال هذه السنوات الخمس محصورة ضمن المجال (70.4% - 99.5%)، وتبين من خلال دراستنا الاحصائية بواسطة برنامج SPSS أن كفاءة المعالجة البيولوجية تكون أفضل ضمن المجال (1,2-3) للنسبة COD/BOD5 ولكنها أظهرت انخفاض تأثير هذه النسبة على كفاءة إزالة BOD5 خلال الفترة (2007-2011) وذلك بسبب انتظام عمل المحطة واستقرار وضع السكان ونوعية وكمية التدفقات القادمة للمحطة كما أن الكفاءة ترتبط أيضاً بمتغيرات كثيرة أهمها بارامترات تشغيل أحواض التهوية.